Silencing of the tomato Sugar Partitioning Affecting protein (SPA) modifies sink strength through a shift in leaf sugar metabolism - Bermudez Salazar, Luisa Fernanda (2014)
Limitations in our understanding about the mechanisms underlying source-sink assimilate partitioning are increasingly becoming a major hurdle for crop yield enhancement via metabolic engineering. By means of a comprehensive approach, this work reports the functional characterization of a DnaJ chaperone related-protein (named as SPA; sugar partition-affecting) involved in assimilate partitioning in tomato plants. SPA protein was found to be targeted to the chloroplast thylakoid membranes. SPA-RNAi tomato plants produced more and heavier fruits, thus resulting in a considerable increment in harvest index. The transgenic plants also displayed increased pigment levels and reduced sucrose, glucose and fructose contents in leaves. Detailed metabolic and enzymatic activities analyses showed that sugar phosphate intermediates are increased while the activity of phosphoglucomutase, sugar kinases and invertases are reduced in the photosynthetic organs of the silenced plants. These changes would be anticipated to promote carbon export from foliar tissues. The combined results suggest that the tomato SPA protein plays an important role in plastid metabolism and mediates the source-sink relationships by affecting the rate of carbon translocation to fruits.